THE IMPACT OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR BASED SPIRITUAL LEADERSHIP ON JOB SATISFACTION - Putra, Julian Perdana; Khan, Ryan Basith Fasih (LPPM STIE Muhammadiah Bandung, 2023)
Spiritual leadership carried out by leaders who have good personal qualities will create harmonious relationships between superiors and subordinates, reward subordinates who achieve objectively, are able to solve problems faced in the organization, and will have an impact on work. Therefore, spiritual leadership and Organizational Citizenship Behavior (OCB) have an important role in achieving the goals of an organization. The aim of this research is to find out how spiritual leadership influences job satisfaction through organizational citizenship behavior (OCB) as a mediating variable in Madiun Regency Population and Civil Registration Service employees in 2023. This research method uses a quantitative approach and collects primary data using a questionnaire. The population and sample in this study amounted to 100 samples. The variables used are spiritual leadership (X), job satisfaction (Y), and organizational citizenship behavior (Z). The analysis tool used is SmartPLS 4.0. The research results show that spiritual leadership (X) has a positive and significant effect on organizational citizenship behavior (Z). Organizational citizenship behavior (Z) has a positive and significant effect on job satisfaction (Y). Spiritual leadership (X) has a positive and significant effect on job satisfaction (Y). Spiritual leadership (X) has a positive and significant influence on job satisfaction (Y) through organizational citizenship behavior (Z) at the Population and Civil Registration Service of Madiun Regency in 2023.